Disease incidence and molecular diversity of Tungro Virus on Rice (Oryza sativa) in Bengkulu, Indonesia - Sutrawati, M.; Ganefianti, D. W.; Sipriyadi, S.; Wibowo, R. H.; Agustin, Z.; Listihani; Selangga, D. G. W. (International Journal of Agricultural Technology, 2021)
There has been no updating data on the incidence of viral diseases that attack rice plants in Bengkulu. Updating data on viral disease distribution status is an initial step to prevent disease outbreaks. The disease incidence and molecular characterization of the tungro virus in Bengkulu, Indonesia wasc reported. Detection of viruses from field samples was amplified Rice Tungro Spherical Virus (RTSV) and could not be amplified RTSV from other field samples. Specific DNA fragments of ±787 bp were successfully amplified using specific primers for the coat protein gene of RTSV. Spesific DNA fragments of 1400 bp were succesfully amplified from Rejang Lebong, Bengkulu Tengah, Bengkulu Utara, and Bengkulu city using Rice Tungro Bacciliform Virus (RTBV) spesifics primers DAF and DAR. The results showed that the RTBV rice isolates from Bengkulu Utara and Rejang Lebong were closely related to the RTBV Seberang Perai isolates from Malaysia (MK552377)